Humour and Sociolinguistic Innovation in Nigerian Social Media: A Study of Selected Whatsapp Messages - Raphael Idowu Ibiowotisi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The increasing use of social media has transformed patterns of communication in Nigeria, creating digital spaces where humour has become an important medium for linguistic creativity, identity construction, and social interaction. Among these platforms, WhatsApp occupies a central position because it enables users to exchange humorous messages that reflect everyday experiences, cultural values, and contemporary social realities. Despite the growing body of research on digital discourse, limited scholarly attention has been given to the role of humour in promoting sociolinguistic innovation within Nigerian WhatsApp communication. This study therefore examined how humour contributes to sociolinguistic innovation in selected Nigerian WhatsApp messages. The study adopted a qualitative research design, drawing on a corpus of one hundred humorous WhatsApp messages, from which thirty representative excerpts were purposively selected for detailed analysis. Data were analysed thematically using Van Dijk's Sociocognitive Theory to explain the interaction between language, shared knowledge, and social context in the production and interpretation of humorous discourse. The findings reveal that humour stimulates code-switching, code-mixing, lexical innovation, semantic extension, figurative language, and multimodal communication through emojis and other digital resources. The study further establishes that humorous WhatsApp messages function as important vehicles for identity construction, cultural expression, social criticism, and the negotiation of everyday experiences within Nigeria's multilingual society. It concludes that WhatsApp has become a dynamic sociolinguistic environment where humour not only entertains but also accelerates language change and enriches contemporary digital communication. The study contributes to sociolinguistic scholarship by demonstrating that humour is a significant catalyst for linguistic innovation in Nigeria's rapidly evolving digital landscape.